THE EFFECTIVENESS OF ELECTRONIC-BASED VILLAGE FINANCIAL ADMINISTRATION MANAGEMENT IN THE SI MANIS DESA APPLICATION (STUDY IN KARANGREJO VILLAGE, GEMPOL DISTRICT, PASURUAN REGENCY) - Rahmani, Mella Anaya; Choiriyah, Ilmi Usrotin (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to analyze the effectiveness level of electronic-based village financial administration management in the implementation of the Si Manis application in Karangrejo Village. With a focus on village development financial management. This study also aims to evaluate the use of the Si Manis application in Karangrejo Village on the quality or impact provided by the Si Manis Application to the Karangrejo Village Government. Method: The research approach used in this study is qualitative research with a descriptive approach. The focus of this study is the effectiveness of financial administration management in the Si Manis Village Application in Karangrejo Village, based on the theory of effectiveness according to Champbell (1989) to measure the success of a program's effectiveness, which contains variables of program success, program target accuracy, program goal achievement, and program monitoring. Results: The results of this study indicate that the use of the Si Manis application in Karangrejo Village has succeeded in increasing the effectiveness of recording financial reports for Karangrejo Village Development. And the results of this study are in line and in accordance with the theory according to Champbell (1989) which contains 4 indicators in determining the level of effectiveness of a program. Novelty: This study provides a new and significant contribution to valid data results because it uses new data and sources. This research also presents novelties by specifically examining the effectiveness of the Si Manis application in Karangrejo Village. It also provides recommendations based on local data that can serve as a reference for developing electronic-based village financial administration management policies in other regions.